Initial stops in Hittite (with an excursus on the spelling of stops in Alala Akkadian) - Kloekhorst, Alwin (Zeitschrift für Assyriologie und vorderasiatische Archäologie, 2010)
In this article it is argued that in Hittite the members of the sign pairs ta vs. da, ka vs. ga and ke/i vs. ge/i represent phonologically distinct sounds in word-initial position. The signs ta and da represent a normal fortis and a glottalized fortis stop, respectively: ta = /ta/ vs. . The signs ka and ke/i, on the one hand, and ga and ge/i, on the other, represent a fortis and a lenis stop, respectively: ka and ke/i = /k-/ vs. ga and ge/i = /g-/. The distribution of the fortis and lenis stops in word-initial position in Hittite is then compared to the situation in the Luwic branch. Moreover, it is argued that the phonetic values of these signs directly reflect their value as attested in the Old Babylonian texts from Alala VII.